SIXN Enterprise: portable dustbin sink / Najihah Zakariya [et al.] - Zakariya, Najihah; Saharuddin, Nur Syazwani; Jamal, Nurkamelia; Atan, Nurhaslin; Roslee, Nor Ain Najwa; Mohd Asri, Munira Atikah (2017)
Our company were working on a project named 'PORTABLE DUSTBIN SINK' The base features that we have use on our product were the portable dustbin, steel tray, water pump and the water tap that will complete the features of the portable dustbin sink.